The effect of shareholder-debtholder conflicts on corporate tax aggressiveness: Evidence from dual holders - Francis, Bill; Teng, Haimeng; Wang, Ying; Wu, Qiang (Journal of Banking & Finance, 2022)
We investigate the effect of agency conflicts between shareholders and debtholders on aggressive tax avoidance using a unique setting of dual holders who simultaneously hold equity and debt of the same firms. We find robust evidence that firms with dual holders exhibit more aggressive tax behavior even after controlling for endogeneity, suggesting that shareholder-debtholder conflicts induce firms to underinvest in tax aggressiveness. In addition, there exists a concave relation between tax aggressiveness and dual owners’ debt exposure relative to their overall debt and equity exposures to the investee firms. Further tests show that the effect of dual ownership on tax aggressiveness is more pronounced among firms with higher risk-shifting tendencies and higher managerial risk-taking incentives. Finally, our bond borrowing cost test shows that dual holdings mitigate the increased cost of borrowing due to aggressive tax avoidance.